A Study on Marketing Strategies for Mobile Online Games from the Perspective of Consumer Behavior - Leng, Ziming (International Journal of Global Economics and Management, 2024)
This study aims to investigate the factors influencing the marketing of mobile online games from the perspective of consumer behavior and provide practical marketing strategies for companies whose main business is mobile online games. By reviewing relevant literature on the development of consumer behavior theory and analyzing consumer behavior, this study identifies the factors that affect marketing strategies for mobile online games. The research findings suggest that successful mobile online game marketing requires a comprehensive consideration of consumer demands, competitor analysis, and brand positioning, as well as the implementation of targeted strategies. By integrating brand strategies, pricing strategies, channel strategies, and marketing strategies, mobile online games can be effectively promoted and attract more users. These strategies not only provide valuable references and insights for mobile online game companies to gain a competitive advantage in highly competitive market environments but also open up new perspectives and directions for future research in related fields.